The effect of lesson study approach on developing teachers’ reflective thinking as a self-assessment tool - Al-Hattami, Abdulghani; Bawaneh, Ali Khaled (Institute of Advanced Engineering and Science, 2024)
Lesson study approach is a professional development strategy used by teachers to improve students’ learning through collaboration and continuous improvement of teaching practices. Studies have shown that implementing a lesson study can increase teacher efficacy, improve students’ achievement, and positively impact school culture. The aim of the research is to examine the effect of using lesson study strategy on developing reflective thinking among teachers. The study applied an experimental design on a sample consisting of 96 (55 experimental group, 41 control group) teachers. A validated reflective thinking questionnaire was used to collect data. The results showed that there are statistically significant differences in favor of the group participated in the lesson study, with a high effect size of 0.84. The results also showed that there are no statistically significant differences attributable to teachers’ experience or the educational level. The paper concludes with a set of recommendations, highlighting the significance of endorsing school-based professional development through lesson study. The adoption of this method is considered crucial in promoting reflective thinking among teachers.